2002
DOI: 10.4269/ajtmh.2002.66.273
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic load and histopathology of cutaneous lesions, lymph node, spleen, and liver from BALB/c and C57BL/6 mice infected with Leishmania mexicana.

Abstract: The course of infection, parasitic loads, and histopathology of cutaneous lesions, draining lymph node, spleen, and liver were compared in BALB/c and C57BL/6 mice over a period of 34 weeks after inoculation in footpad with promastigotes of a Leishmania mexicana reference strain. The results show that the primary footpad lesions first present a 12-week phase that develops similarly in both strains of mice. Thereafter, a cutaneous and visceral dissemination of L. mexicana parasites occurs in BALB/c mice; the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Fig. 1A shows that lesions in WT mice never healed during the 97-day period of infection, compatible with previous reports on the incapacity of these animals to cure L. amazonensis infection (Song et al 1997, Aguilar Torrentera et al 2002a, Maioli et al 2004). IFN-γ deficiency did not lead to more progressive disease at least during the first two months of infection, as seen by the comparable lesion sizes of IFN-γ KO mice and WT mice.…”
Section: Role Of Ifn-γ During L Amazonensis Infection -The Course Ofsupporting
confidence: 89%
“…Fig. 1A shows that lesions in WT mice never healed during the 97-day period of infection, compatible with previous reports on the incapacity of these animals to cure L. amazonensis infection (Song et al 1997, Aguilar Torrentera et al 2002a, Maioli et al 2004). IFN-γ deficiency did not lead to more progressive disease at least during the first two months of infection, as seen by the comparable lesion sizes of IFN-γ KO mice and WT mice.…”
Section: Role Of Ifn-γ During L Amazonensis Infection -The Course Ofsupporting
confidence: 89%
“…Various studies have reported a resistance of C57BL/6 mice and a susceptibility of BALB/c mice to parasitic infections (12,13), including trypanosomiasis (14). In addition, it was previously shown that NO production by macrophages from infected C57BL/6 mice is greater than that from BALB/c mice (15,16), and a correlation between the level of NO production and the susceptibility of mouse strains to parasitic infections has been suggested.…”
mentioning
confidence: 99%
“…It remains to be elucidated whether the infiltration of lymph nodes and spleen, the key organs controlling the parasite dissemination by Leishmania infected macrophages during an experimental infection in animals is the cause or the consequence of the final breakdown of the microarchitecture of T-and B-cell areas (Saito et al, 1996). Bloodstream dissemination of the parasite to internal organs and probably t o other cutaneous tissues was reported to be due to the destruction of the lymphoid tissue and the lymph node capsule leading to the invasion of capillaries by the infected macrophages, as well as parasites in the red pulp of spleen and portal space of the liver (Aguilar-Torrentera et al, 2002). Donnelly et al (1998) studied the histological characterization of cutaneous leishmaniosis in BALB/c mice experimentally infected with L. major and C3H mice with L. braziliensis.…”
Section: Resultsmentioning
confidence: 99%